Biodegradation of Polybrominated Diphenyl Ethersin Liquid Media and Sewage Sludge by Trametes versicolor - Vilaplana Artigas, Marcel (2015)
Polybrominated diphenyl ethers (PBDE) are widely employed as flame retardants and constitute a group of emerging pollutants of high persistence. The degradation of different PBDE commercial mixtures (penta-, octa- and deca-BDE) by the white-rot fungus Trametes versicolor under aerobic conditions was studied. This work demonstrates the capacity of T. versicolor to degrade three different PBDE commercial mixtures in aqueous phase, obtaining final removal efficiencies of 87±6, 85±13 and 67±7% for deca-, pentaand octa-BDE mixtures (and minimal degradation of 73±5, 38±13, and 28±7%), respectively. The intracellular enzymatic complex cytochrome P-450 is proposed as the enzyme involved in the first step of deca-BDE degradation by T. versicolor. In an effort to assay the application of the fungus in real contaminated matrices, the study successfully demonstrated the ability of T. versicolor to degrade pre-existent deca-BDE from sewage sludge in a solid-phase treatment, reaching 86% elimination at the end of the process. The findings support the potential use of the ligninolytic fungus in bioremediation of PBDE.